Proyecto de factibilidad para la implementación de un camal avícola y comercialización de pollo pelado en el cantón Catamayo - Garzón Carrión, Doris Elizabeth (2015)
This thesis was conducted to determine the feasibility of implementing a poultry slaughterhouse and marketing of peeled chicken in Canton Catamayo, of the Province of Loja; by reference to the consumption of chicken in our country and city is the majority and that is on the rise because the meat is one of the healthiest and most economical. To make this thesis was first used some data, which were provided by the INEC, as well as some methods of investigation, among the most prominent were the statistician who allowed us to do different projections; the same that gave us the estimate of the population of the canton Catamayo, which was projected for 2015, which is 33,712 inhabitants, also through the mathematical method could calculate the population sample, resulting in a total of 382 people surveyed; Also we use the survey to determine the supply and demand of chicken consumption in the canton Catamayo; The survey was applied to consumers specifically to 382 people, as well as those marketed chicken in a total of 40. On the other hand the method used in observation to determine the best place for both the slaughtering plant to the local distribution, thus leaving the poultry slaughterhouse in Catamayo is green cane sector 2 Km from the ring road to the coast and local for distribution will be located in the streets Eugenio Espejo between May 24 and November 18, since places meet the necessary requirements. The project starts with an initial investment of USD. 117,400 of which $ 80,000.00 representing 68.14% are own contributions; and a loan with a value of $ 37,398.24 which means 31.84% Its total costs are USD. 41,995.40and estimated revenues are USD 530,394.48 this for your first year. Also, in the income statement and cash flow positive balances for the 10 year life of the project it is obtained. With regard to financial study calculated the Net Present Value is 510,330.50; the internal rate of return is 43.99% (higher than the market rate of 10.21% chance), Benefit Cost Ratio is USD. 0.20 profit for each dollar invested, the Capital Recovery Period occurs in 4 years, 2 months; and the sensitivity analysis of the project is 12.15% on increased costs, and 1% in reducing their income. Completed all stages of the project it was concluded the feasibility of the creation of the company's chicken slaughtering and marketing in the canton Catamayo